Benefits of transmission switching and energy storage in power systems with high renewable energy penetration - Peker, Meltem; Kocaman, Ayse Selin; Kara, Bahar Y. (Applied energy, 2018)
•A stochastic programming approach is proposed to model TS and ESS sizing simultaneously.•The model considers DSM and renewable energy curtailment policies with various limits.•The effect of TS on total cost, sizes, locations of ESS are discussed.•We find that TS is noteworthy to analyze for power systems with renewable targets. Increasing the share of renewable energy sources in electricity generation helps address concerns about carbon emissions, global warming and energy security (i.e. dependence on fossil fuels). However, integrating intermittent and variable energy sources into the grid imposes new challenges for power system reliability and stability. To use these clean sources in electricity generation without endangering power systems, utilities can implement various control mechanisms, such as energy storage systems, demand side management, renewable energy curtailment and transmission switching. This paper introduces a two-stage stochastic programming model that co-optimizes transmission switching operations, and transmission and storage investments subject to limitations on load shedding and curtailment amounts. We discuss the effect of transmission switching on the total investment and operational costs, siting and sizing decisions of energy storage systems, and load shedding and renewable energy curtailment in a power system with high renewable penetration. An extensive computational study on the IEEE 24-bus power system with wind and solar as available renewable sources demonstrates that the total cost and total capacity of energy storage systems can be decreased up to 17% and 50%, respectively, when transmission switching is incorporated into the power system.